Does missiology have three legs to stand on? The upsurge of interdisciplinarity. (January 2016) - Nehrbass, Kenneth
A common heuristic device for depicting the interdisciplinary nature of missiology is the metaphor of a stool that stands on three legs (or academic disciplines). However, missiologists have disagreed on exactly which disciplines comprise those legs. That theology is central is hardly contested; but there is less agreement about the role of the social sciences, history, education, mission strategy, and so forth. Here, I argue that we should move beyond the three-legged stool metaphor, as it fails to describe the true interdisciplinary nature of missiology: The academic influences on missiology are more numerous than the stool metaphor allows for; the borders between these disciplines are fuzzy and changing; and the influence of academic theories on mission strategy is not merely one-way. In quest of a more satisfactory metaphor, I begin by suggesting a definition of missiology as the utilization of multiple academic disciplines to develop strategies for making disciples across cultures. Drawing on that definition, I develop the image of missiology as a river with countless tributaries (theoretical disciplines) that converge for this common goal. Since scholars of Christian mission cannot be experts in many fields, we must be intentional with the sort of interdisciplinarity that is most useful for designing effective mission strategies.